Automation of update of digital national geo‐reference databases - Stankevičius, Žilvinas; Beconytė, Giedrė; Kalantaitė, Aušra (Technological and Economic Development of Economy, 2010)
Unified geo‐reference data model is a very important part of national geographic information management. It has been developed within the project of Lithuanian geographic information infrastructure in 2006–2008. This model allows automated integration of large scale (mainly municipality) geo‐reference data into the unified national geo‐reference database. It is based on unique object identifiers across all geo‐reference databases and on standard update and harmonisation procedures. The common stages of harmonisation of geo‐reference databases at different scales include: implementation of a unique identifier of geographic objects across all databases concerned; definition of the life cycle of the objects; definition of cohesion boundary and of the harmonisation points along the boundary; maintenance of the local database and automatic update of the national database using special service. When implemented, such model will significantly facilitate maintenance of national geo‐reference database and in five years from full implementation will have a significant economic effect.Article in English.Nacionalinių georeferencinių duomenų bazių atnaujinimo automatizavimasSantrauka. Lietuvoje atlikta savivaldybėse kaupiamų erdvinių duomenų analizė parodė, kad tik didesniu miestų savivaldybės kaupia erdvinius duomenis, tačiau erdvinių duomenų sandaros skirtingos. Nacionaliniu lygmeniu kuriamos erdviniu duomenų bazės nesuderintos tarpusavyje, dubliuojamas erdviniu duomenų kaupimo procesas, orientuojantis į skirtingų masteliu žemelapių gamyba. Bendras georeferenciniu duomenų modelis (VGDM) apima georeferencinių duomenų konversija iš įvairių mastelių oficialių geografinių duomenų rinkinių, o ypač iš savivaldybių georeferencinių duomenų rinkinių į bendrą valstybės georeferencinių duomenų bazę (VGDB) ir nuolatinės VGDB atnaujinimo procedūras. VGDB atnaujinimo technologijos pagrindas ‐ geoobjektų (vektorinių geografinių duomenų elementų) egzistavimo ciklas ir pokyčių sekimas. Georeferencinių duomenų modelis reiškia, kad yra numatytas kelias pasiekti efektyvią įvairių mastelių oficialių duomenų bazių sąveiką.Reikšminiai žodžiai: kartografija, GIS, geografiniu duomenų modeliai, georeferenciniai duomenys, atnaujinimo servisas, darninimas.First published online: 09 Jun 2011